ประสบการณ์ของพยาบาลวิชาชีพที่ปฏิบัติงานในหน่วยบริการการแพทย์ฉุกเฉิน - จิระทวี สมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this research was to describe the experiences of professional nurses working at emergency medical services. This qualitative research used a framework based on phenomenological approach of Heidegger. Fourteen professional nurses who had experience working in emergency medical services were willing to participate in this study. Data were collected through interviews and observation, and analyzed by using content analysis of Crist and Tanner method. The findings of nurses’ work at emergency medical services were consisted of 4 categories: 1. Providing emergency services outside a hospital including 3 sub-categories as follows: 1.1) performing resuscitation, 1.2) preparing for emergency helps during mass meetings, and 1.3) focusing on teamwork. 2. Preparing to perform services including 4 sub-categories as follows: 2.1) maintaining good physical health, 2.2) getting ready oneself, 2.3) gaining knowledge for work, and 2.4) sharing information among team members to improve services. 3. Working under limited time but keeping good services including 7 sub-categories as follows: 3.1) checking the preparation of medical equipments, 3.2) assessing details of patients’ sign and symptoms before going to help, 3.3) concerning safety first, 3.4) solving urgent problems, 3.5) referring patients to a hospital, 3.6) caring for patients’ family members, and 3.7) writing a report and rechecking medical equipments. 4. Reflecting psychological outcomes including 3 sub-categories as follows: 4.1) challenging nurses’ ability, 4.2) feeling good if patients were safe, and 4.3) feeling sad if unable to save patients’ life.